Medicare Advantage and Fee‐for‐Service Performance on Clinical Quality and Patient Experience Measures: Comparisons from Three Large States. (12th November 2017) - Timbie, Justin W.; Bogart, Andy; Damberg, Cheryl L.; Elliott, Marc N.; Haas, Ann; Gaillot, Sarah J.; Goldstein, Elizabeth H.; Paddock, Susan M.
Abstract : Objective: To compare performance between Medicare Advantage (MA) and Fee‐for‐Service (FFS) Medicare during a time of policy changes affecting both programs. Data Sources/Study Setting: Performance data for 16 clinical quality measures and 6 patient experience measures for 9.9 million beneficiaries living in California, New York, and Florida. Study Design: We compared MA and FFS performance overall, by plan type, and within service areas associated with contracts between CMS and MA organizations. Case mix‐adjusted analyses (for measures not typically adjusted) were used to explore the effect of case mix on MA/FFS differences. Data Collection/Extraction Methods: Performance measures were submitted by MA organizations, obtained from the nationwide fielding of the Medicare Consumer Assessment of Healthcare Providers and Systems (MCAHPS) Survey, or derived from claims. Principal Findings: Overall, MA outperformed FFS on all 16 clinical quality measures. Differences were large for HEDIS measures and small for Part D measures and remained after case mix adjustment. MA enrollees reported better experiences overall, but FFS beneficiaries reported better access to care. Relative to FFS, performance gaps were much wider for HMOs than PPOs. Excluding HEDIS measures, MA/FFS differences were much smaller in contract‐level comparisons. Conclusions: Medicare Advantage/Fee‐for‐Service differences are often large but vary in important ways across types of measures and contracts.